Документи з особового фонду Андрія Жука (частина 2) - Пилипенко, О. (Сiверянський літопис, 2020)
Мета дослідження – запровадження до наукового обігу нових, раніше не опублікованих архівних матеріалів початку ХХ ст. та періоду національно-визвольних змагань в Україні. Наукова новизна роботи зумовлена підготовкою та уведенням до наукового обігу раніше невідомих джерел з особового фонду Андрія Ілліча Жука – видатного українського революціонера часів УНР, громадсько-політичного діяча, одного з перших фундаторів кооперативних організацій на українських землях. Ці документи зберігаються у фонді № 3807 Центрального державного архіву вищих органів влади та управління України у м. Києві (ЦДАВО України). До них належать, зокрема, фрагменти неопублікованого епістолярію, рукописів А. І. Жука і програмних документів партій, товариств, автором яких він був. Їхня публікація дозволяє науковцям з'ясувати особливості українського суспільно-політичного руху початку XX ст. Наведені документи дозволяють проаналізувати активну суспільно-політичну діяльність Андрія Ілліча Жука, детальніше познайомитися з політичними поглядами, переконаннями, життєвою позицією видатного революціонера і державного діяча Української Народної Республіки 1917–1921 рр. У другій частині публікації ми продовжуємо запроваджувати до наукового обігу документи, які висвітлюють діяльність Андрія Ілліча Жука в галузі видавничої справи. Сподіваємось, що ці джерела будуть корисні фахівцям, які досліджують історію України першої половини ХХ ст., джерелознавцям, краєзнавцям, оскільки вони проливають світло на окремі сторінки нашої славетної історії. Документи подано зі збереженням особливостей мови, орфографії, пунктуації оригіналів. The purpose of the study is to introduce into the circulation of new, previously unpublished, archival materials of the early twentieth century and the period of national liberation competitions in Ukraine. Documents from the personal fund of Andriy Zhuk – a prominent Ukrainian revolutionary of Ukrainian Publik Republik times, a famous public-political figure, one of the first foundations of cooperative and other organizations on Ukrainian lands, which are stored in the Central State Archives of Higher Authorities and Administratio of Ukraine in Kyiv (CSA of Ukraine) and cover the activities of members of the Union of Liberation of Ukraine. The Documents cover the active socio-political activity of Andriy Illich Zhuk allow us to get aquainted with this aspects of his life activity. These documents cover the active socio-political activity of Andriy Illich Zhuk, allow us to get acquainted with his political views, beliefs, life position of the prominent revolutionary and statesman of the Ukrainian People’s Republic 1917–1921. In the second part we continue to introduce the documents activity of Andriy Zhuk in the field of publishing. Ukraine of the first half of the twentieth century, to Source historians, local historians, because they shed light on some pages of our glorious history. Documents are submitted with languge preservation, spelling punctuation of the originals. The scientific novelty of the work is conditioned by the preparation of the publication and the introduction into the scientific circulation of previously unknown sources from the personal fund of Andriy Illich Zhuk. The introduction into scientific circulation of documents of the archive fund No. 3807, in particular the unpublished epistolary, the manuscripts of A. Zhuk and the program documents of the parties, the societies of which he was the author, allows scholars to study the features of the Ukrainian sociopolitical movement of the early XX century.